Evaluasi Efektivitas dalam Meningkatkan Pemahaman dan Mengurangi Miskomunikasi Antar Budaya - Dwi Anggraini Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Intercultural communication is becoming increasingly important in this era of globalization, where interactions between individuals and groups from different cultural backgrounds are increasingly common. This article will review various theories and concepts related to intercultural communication, identify factors that influence its effectiveness, and analyze how effective communication can contribute to improving understanding and minimizing miscommunication. In addition, this article will also discuss the challenges that may arise in intercultural communication and strategies to overcome them. Through literature studies and analysis of previous studies, this article is expected to provide comprehensive insights into the crucial role of intercultural communication in building harmonious and productive relationships amidst cultural diversity.